Adduct Formation, B−H Activation and Ring Expansion at Room Temperature from Reactions of HBcat with NHCs. Issue 37 (9th August 2016) - Würtemberger‐Pietsch, Sabrina; Schneider, Heidi; Marder, Todd B.; Radius, Udo
Abstract: We report the reactions of catecholborane (HBcat;1 ) with unsaturated and saturated NHCs as well as CAAC Me . Mono‐NHC adducts of the type HBcat⋅NHC (NHC= n Pr2 Im, i Pr2 Im, i Pr2 Im Me, and Dipp2 Im) were obtained by stoichiometric reactions of HBcat with the unsaturated NHCs. The reaction of CAAC Me with HBcat yielded the B−H activated product CAAC Me (H)Bcat via insertion of the carbine‐carbon atom into the B−H bond. The saturated NHC Dipp2 SIm reacted in a 2:2 ratio yielding an NHC ring‐expanded product at room temperature forming a six‐membered −B−C=N−C=C−N− ring via C−N bond cleavage and further migration of the hydrides from two HBcat molecules to the former carbene‐carbon atom. Abstract : It's all about the carbene ! The isolation and detailed structural characterization of a series of adducts of catecholborane (HBcat) with backbone unsaturated N ‐heterocyclic carbenes (NHCs), a B−H activation product with a cyclic (alkyl)(amino)carbene CAACMe, and a ring expanded product with a backbone saturated NHC is reported. The mono‐NHC adducts and the B−H activation product are stable at higher temperatures, whereas the product of the reaction of HBcat with the saturated NHC undergoes a rearrangement even at room temperature, forming a six‐membered heterocyclic ring.